Impact of ESKAPE Pathogens on Bacteremia: A Three-Year Surveillance Study at a Major Hospital in Southern Italy - Mariagrazia De Prisco; Roberta Manente; Biagio Santella; Enrica Serretiello; Federica Dell'Annunziata; Emanuela Santoro; Francesca F. Bernardi; Chiara D'Amore; Alessandro Perrella; Pasquale Pagliano; Giovanni Boccia; Gianluigi Franci; et al. (MDPI AG, 2024)
Background/Objectives: ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) pose a serious public health threat as they are resistant to multiple antimicrobial agents. Bloodstream infections (BSIs) caused by ESKAPE bacteria have high mortality rates due to the limited availability of effective antimicrobials. This study aimed to evaluate the prevalence and susceptibility of ESKAPE pathogens causing BSIs over three years in a large tertiary hospital in Salerno. Methods: Conducted at the Clinical Microbiology Laboratory of San Giovanni di Dio e ''Ruggi D'Aragona'' Hospital from January 2020 to December 2022, blood culture samples from different departments were incubated in the BD BACTEC™ system for 5 days. Species identification was performed using MALDI-TOF MS, and antimicrobial resistance patterns were determined by the VITEK2 system. Results: Out of 3197 species isolated from positive blood cultures, 38.7% were ESKAPE bacteria. Of these, 59.9% were found in blood culture samples taken from men, and the most affected age group was those aged >60 years. (70.6%). Staphylococcus aureus was the main BSI pathogen (26.3%), followed by Klebsiella pneumoniae (15.8%). Significant resistance rates were found, including 35% of Staphylococcus aureus being resistant to oxacillin and over 90% of Acinetobacter baumannii being resistant to carbapenems. Conclusions: These results highlight the urgent need for antimicrobial stewardship programs to prevent incurable infections.